SAT0197 Biological Therapy and Radiosynoviorthesis in Patients with Rheumatoid Arthritis. (9th June 2015) - Szentesi, M.; Nagy, Z.; Geher, P.
Abstract : Background: The treatment of patients with rheumatoid arthritis (RA) has been spectaculary changed since the 1950's. Introduction of the steroid compounds and their local application, the chemical and radionuclide synovectomy, surgical synovectomy, use of non steroid drugs, the basic treatment and the spread of biological therapy are the most important steps. Introduction of the biological therapy has changed the quality of life for these patients. Objectives: During biological therapy sometimes 1 or 2 joints could be affected by inflammation. In this cases always the question is how to solve the problem. Change of the biological or basic therapy, use surgical synovectomy or radiosynovectomy (RSO)? Methods: In our reumatological department 1500 patients with RA were treated with biological therapy between 2002 and 2014. In 100 patients we applied RSO because of the inflammation of the knee joint during biological therapy. We made a long term follow-up in 62 patient. All participants provided written informed consent. In all participants inflammatory knee joint disease was diagnosed on the basis of the American College of Rheumatology. 55 of 62 patients with rheumatoid arthritis were seropositive, 7 seronegative. Mean age of 8 male and 56 female patients was 51.4 years (range 24-79) years. In 32 patients the right knee, in 30 the left knee was treated by radiosynovectomy. Steinbrocker functional stadium II was observed in 52, stadium III in 10. Mean duration of disease was 7.3 years (range 0.5-25), of synovitis (6.3month (range 3-8) Mean number of punctions of the treated joint prior to radiosynovectomy was 4, 2 per patient and of steroid administrations prior to radiosynovectomy 3, 0. In 12 patients a systemic steroid therapy has been performed. Results: During the study period, inflammation decreased. In the first two years excellent and good results were recorded in 82, 2%. Two years after radiosynoviorthesis 83.3% of patients did not need another punction. Before the knee inflammation patients were in complete remission which status has been achieved after RSO as well. DAS: 2, 4±0, 4. Conclusions: RSO is an effective method to treat the inflammation of the knes. The RSO performed during biological tehrapy is as effective as in the case of patients without biological therapy. In case of a succesful RSO there is no need for biological or basic therapy neither for surgical synovectomy. However an intraarticular injection has a low risk for infection it is recomended to avoid the biological therapy during the RSO. Disclosure of Interest: None declared